2004
DOI: 10.1007/bf03340906
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Positive Outcomes for Students With Emotional Disturbance

Abstract: This longitudinal study assessed changes in skills for students with emotional disturbance (ED) over a one-year time period in a private special education school and examined variables that predicted positive outcomes for these students. At Time 1, teachers rated 84 students with ED using standardized behavior rating scales to assess problem severity and skills for predicting inclusion. Information was also obtained about students' school behavior from the school's behavioral level system. One year later (Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“…Given that the classroom teacher plays a critical role in developing the classroom atmosphere, the inclusion of strength-based assessment for students with EBD within the context of a psychoeducational report may serve as a foundation for a more positive educational environment for these students. Students with EBD have been found to possess multiple strengths, despite severity of impairment (Nickerson, Brosof, & Shapiro, 2004;Walrath, Mandell, Holden & Santiago, 2004), suggesting that the use of strengthbased measures with this population may be effective in calling attention to the frequently overlooked assets these students possess.…”
mentioning
confidence: 99%
“…Given that the classroom teacher plays a critical role in developing the classroom atmosphere, the inclusion of strength-based assessment for students with EBD within the context of a psychoeducational report may serve as a foundation for a more positive educational environment for these students. Students with EBD have been found to possess multiple strengths, despite severity of impairment (Nickerson, Brosof, & Shapiro, 2004;Walrath, Mandell, Holden & Santiago, 2004), suggesting that the use of strengthbased measures with this population may be effective in calling attention to the frequently overlooked assets these students possess.…”
mentioning
confidence: 99%
“…One study reported that the use of level system data was effective as one of several predictors of future school performance (Nickerson, Brosof, & Shapiro, 2004 ). In general, teachers have positive views concerning the level system and its effect on student behavior.…”
mentioning
confidence: 99%